U.K. standards of care for occupational contact dermatitis and occupational contact urticaria - Adisesh, A (Blackwell Publishing Ltd, 2013)
The diagnosis of occupational contact dermatitis (OCD) and occupational contact urticaria (OCU) is a process that involves fastidious clinical and occupational history taking, clinical examination, patch testing and skin-prick testing. A temporal relationship of work and/or the presence of a rash on the hands only raises suspicion of an occupational cause, and does not necessarily confirm an occupational causation. The identification of allergy by patch or prick tests is a major objective, as exclusion of an offending allergen from the environment can contribute to clinical recovery in the individual worker and avoidance of new cases of disease. This can be a complex process where allergens and irritants, and therefore allergic and irritant contact dermatitis, may coexist. This article provides guidance to healthcare professionals dealing with workers exposed to agents that potentially cause OCD and OCU. Specifically it aims to summarize the 2010 British Occupational Health Research Foundation (BOHRF) systematic review, and also to help practitioners translate the BOHRF guideline into clinical practice. As such, it aims to be of value to physicians and nurses based in primary and secondary care, as well as occupational health and public health clinicians. It is hoped that it will also be of value to employers, interested workers and those with responsibility for workplace standards, such as health and safety representatives. Note that it is not intended, nor should it be taken to imply, that these standards of care override existing statutory and legal obligations. Duties under the U.K. Health and Safety at Work Act 1974, the Management of Health and Safety at Work Regulations 1999, the Control of Substances Hazardous to Health Regulations 2002, the Equality Act 2010 and other relevant legislation and guidance must be given due consideration, as should laws relevant to other countries.